Producción, comercialización y rentabilidad de la mora de castilla (rubus glaucus benth) en la parroquia el tingo la esperanza y su relación con la economía del cantón La Maná provincia de Cotopaxi, año 2011 - Tibanlombo Azogue, José Manuel (2012)
The analysis of Production, Marketing, and Profitability of blackberries was conducted with the purpose of identifying the production of the fruit that is carried out by producers who live in the area of El Tingo-La Esperanza. In order to reach the objectives, it was essential to collect data from producers of blackberries through the application of surveys; then it was proceeded to analyze the extracted data of both producers and consumers from La Maná canton.